A case of bullous pemphigoid in a patient with metastatic melanoma treated with pembrolizumab. Issue 3 (June 2015) - Carlos, Giuliana; Anforth, Rachael; Chou, Shaun; Clements, Arthur; Fernandez-Peñas, Pablo
<x xml:space="preserve">Abstract</x> The innovative blockade of immune checkpoints with targeted immunotherapies, such as monoclonal antibodies against programmed cell death-1, is pioneering the treatment for advanced melanoma. Potential adverse events of particular interest associated with immunotherapy are of an inflammatory or immune-related nature. Reported dermatological side effects mostly comprise nonspecific rash and pruritus. This is a report of a 75-year-old man with metastatic melanoma who was initially administered pembrolizumab at 10 mg/kg every 3 weeks. He developed spongiotic dermatitis that was partially treated with topical steroids after cycle 3. Pembrolizumab cycles were stopped because of disease progression after cycle 6. On the 30-day follow-up, the patient presented with extensive erythematous papules and plaques, in addition to a few intact and ruptured vesicles and bullae over the upper and lower limbs, especially over the knees and elbows. Both punch skin biopsies (haematoxylin and eosin and direct immunofluorescence studies) confirmed a bullous pemphigoid diagnosis. He was treated with a tapering dose of oral prednisone, resulting in rapid clinical improvement after only a week of treatment, which was switched to dexamethasone following the diagnosis of new brain metastases.